(3GdYbjOI GdNGdUI Hjf GdWhjd hGdbUjQs - (3bGSe GdGfOLGfjs
(3ChdgG (B:s
(3hHYO aEfi CQOJ Cf CLeY Hjf GdcJH GdeJaQbI ai GdJhMjO hSdcJ ajgG eSdc GdGNJUGQ Hjf cd eSCdg s
(3BNQgG (B:s
(3hbGd QShd Gddg Udi Gddg Ydjg hSde (B: (3CQHY ef cf ajg cGf efGabkG NGdUkG hef cGfJ ajg NUdI ajgf cGfJ ajg NUdI ef GdfaGb MJi jOYgG EPG ChJef NGf hEPG MOK cPH hEPG YGgO ZOQ hEPG NGUe aLQ (B" (3hUdi Gddg Ydi Bdg hUMHg CLejYf s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdOcJhQ MSjf Ydi eMahX (B(106) s
Keywords: (3GdJhMjO hGdedd hGdfMds